Effects of WeChat follow-up management on the psychological distress, care burden, and quality of life of parents of infants with bronchopulmonary dysplasia: a retrospective cohort study - Shi, Zhong-Shan; Wang, Xin-Bing; Wang, Ming-Cong; Zeng, Yan-Yan (Frontiers in Pediatrics, 2023)
The objective was to explore the impact of WeChat follow-up management on the psychological distress, care burden, and quality of life of parents of infants with bronchopulmonary dysplasia (BPD) receiving in-home care. Methods:This was a retrospective cohort study. A total of 101 parents of infants with BPD who were followed up from January 2016 to January 2022 were included in this study.According to different follow-up methods, these patients were classified into the WeChat group and the routine group. The Depression, Anxiety, and Stress Scale-21 (DASS-21), Zarit Caregiver Burden Interview (ZBI), and WHOQOL-BREF were used. The data on the psychological distress, care burden, and quality of life of the parents in the two groups were analyzed and compared at discharge and at the 3-month follow-up. Results: There was no significant difference in the DASS-21 and ZBI scores at discharge between the parents in the two groups. During the 3-month follow-up, the scores of the DASS-21 anxiety and stress subscale and the ZBI of parents in the WeChat group were significantly lower than those of parents in the routine group (P<0.05); however, there was no significant difference in the depression subscale score between the two groups (P>0.05). A comparison of the WHOQOL-BREF score between the two groups showed that the total quality of life score in the WeChat group was significantly higher than that in the routine group (P<0.05). The scores of the psychological and social relationship fields in the WeChat group were significantly higher than those in the routine group (P<0.05). The incidence of adverse events during follow-up was significantly lower in the WeChat group than in the routine group (P<0.05). Conclusion: WeChat follow-up management is helpful to decrease the anxiety and stress, reduce the care burden, and improve the quality of life of parents of infants with BPD receiving in-home care.